Equation-based congestion control for unicast applications. - Floyd, Sally
This paper proposes a mechanism for equation-based congestion control for unicast traffic. Most best-effort traffic in the current Internet is well-served by the dominant transport protocol, TCP. However, traffic such as best-effort unicast streaming multimedia could find use for a TCP-friendly congestion control mechanism that refrains from reducing the sending rate in half in response to a single packet drop. With our mechanism, the sender explicitly adjusts its sending rate as a function of the measured rate of loss events, where a loss event consists of one or more packets dropped within a single round-trip time. We use both simulations and experiments over the Internet to explore performance.
Keywords: Computing methodologies; Artificial intelligence; Problem Solving, Control Methods, and Search; Control theory; Computer systems organization; Computer communication networks; Network protocols; TCP IP; Local and wide area networks; Internet (e.g., TCP/IP).; Algorithms; Design; Experimentation; Measurement; Performance; Reliability; Standardization; Theory